Tradisi Pembersihan Bende sebagai Sarana Pendidikan Islam di Desa Bumijawa: Studi Nilai Sosial dan Religius - Jannah, Roikhatul; Falah, Syamsul; Amelia, Tri Hikmatul (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to explore and analyze the Bende Cleaning Tradition as a means of Islamic education in Bumijawa Village, focusing on its social and religious values. The research seeks to understand the tradition's process, its perspective within Islamic education, and the educational values embedded in the tradition in Bumijawa Village.Method – This This research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The analysis process included data reduction, data display, and conclusion drawing to ensure a comprehensive understanding of the phenomenon. Findings – The findings indicate that the tradition holds significant spiritual value while also serving as a medium for character education, particularly for younger generations. The purification process of Bende reflects values such as solidarity, gratitude, and social awareness, which align with the Islamic educational principles of morality and ethics. Furthermore, this tradition reinforces community identity and highlights the importance of environmental preservation as a form of stewardship. Research Implications – This study is expected to enhance public awareness of the importance of preserving local traditions that carry educational and religious significance. Additionally, the findings may contribute to the development of an Islamic education curriculum that integrates cultural contexts. The study offers a reference for further research in social studies and Islamic education.